Effect of high Fe doping on Raman modes and optical properties of hydrothermally prepared SnO2 nanoparticles. (April 2018) - Ben Haj Othmen, Walid; Sieber, Brigitte; Elhouichet, Habib; Addad, Ahmed; Gelloz, Bernard; Moreau, Myriam; Szunerits, Sabine; Boukherroub, Rabah
Abstract: Fe-doped tin dioxide nanoparticles SnO2 :Fe (x%) with x ranging from 0 to 20 were elaborated by a performed hydrothermal method. A deep structural study on the obtained nanoparticles was carried out using X-ray diffraction (XRD), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. The XRD measurements revealed that the rutile structure of the SnO2 was kept even for high iron concentrations. It is also observed that when iron amount increases the grain size decreases and the band gap is obviously red shifted. HRTEM imaging shows a good crystallinity of the elaborated NPs and confirm the grain size magnitude deduced from XRD measurements. The Raman modes associated to ferric phases are absent in the Fe-doped spectra which is in agreement with the XRD and HRTEM results proving the formation of SnO2 :Fe solid phase. The Raman A1g mode seems to be strongly affected by the morphology transformation undergone by SnO2 NPs and by the induced local symmetry break when introducing iron. Forbidden Raman phonon modes were detected and an enhancement of the (110) surface oxygen bridging seems to follow the iron doping. This latter structural feature seems to present a major contribution to the notable enhancement of hydroxyl groups' adsorption on the Fe-doped SnO2 surface. The variation of the Urbach energy E u with Fe amount is discussed and is found to be in accordance with the different interpretations. The PL spectra reveals that the UV-violet band of the SnO2 NPs was affected by iron presence and the induced non-systematic variation of this emission was discussed. A decrease in visible emission was noted when introducing iron revealing that Fe doping affects the density of singly charged oxygen vacancies.